Negative autoregulation of c-myc gene expression is inactivated in transformed cells. - Grignani, F (1990)
Negative feedback regulation of c-myc gene expression has been observed in some, but not all, cell types. In order to demonstrate conclusively the existence of this mechanism and gain insight into the cause of its inactivation, we have directly examined its function in B cells and then investigated its activity in a number of cell types. We demonstrate the existence of negative c-myc autoregulation by showing the rapid, dose dependent and reversible suppression of endogenous c-myc expression in EBV-immortalized B lymphoblastoid cells transfected with a c-myc gene expressed under the control of a heavy metal inducible promoter. Autoregulation occurs at the level of transcriptional initiation and is mediated by at least one stable intermediate or cofactor molecule. The c-myc autoregulatory mechanism was found operative in all (11 of 11) non-tumorigenic cells tested, including normal and immortalized lymphocytes and fibroblasts. However, this mechanism was found to be inactive in all (10 of 10) tumor cell lines derived from a variety of tissues including those carrying normal and oncogenically activated c-myc genes. These data establish the existence of an important regulatory circuit modulating c-myc expression in normal cells and suggest that its inactivation may represent a general regulatory disturbance of transformed cells.